The intersection of philosophy of language and artificial intelligence: Challenges in replicating human language understanding: Sooraj Kumar Maurya - Kumar Maurya, Sooraj (Quórum Académico, 2024)
This work explores the intersection between the philosophy of language and artificial intelligence (AI), focusing on how machines process human language. Analyzes theories of meaning, reference, and communication in AI systems and evaluates their ability to address linguistic nuances such as context, ambiguity, and the social use of language. It is noteworthy that although AI can simulate some facets of human language, it lacks thedeep, contextual understanding that characterizes humans. The research concluded that, as AI has advanced significantly, there is a fundamentalgap between the human and artificial ability to understand and use languages in a natural and meaningful way.